Fasies gunung api dan aplikasinya - Bronto, Sutikno (Indonesian Journal on Geoscience, 2006)
http://dx.doi.org/10.17014/ijog.vol1no2.20061Based on the nature and rock association, a composite volcanic cone can be divided into central facies, proximal facies, medial facies and distal facies. Physiographically, those begin from central eruption at the summit, going down to upper slope, lower slope, and foot plain in the surrounding area. Central facies is characterized by the presence of subvolcanic intrusions, lava domes, and hydrothermally altered rocks. Proximal facies consists of alternating lava fl ows and pyroclastic breccias. Medial fasies mainly is composed of pyroclastic breccias, laharic breccias, and conglomerates. Whereas, distal facies is dominated by fi ne-grained epiclastic rocks having sand to clay size. Tuff can be widely distributed from proximal to distal facies due to its fi ne grain and lightness. Methodological approachs for classifi cation of volcanic facies in Tertiary and older rocks are remote sensing and geomorphology, volcanic stratigraphy, physical volcanology, structural geology, and petrology-geochemistry. This volcanic facies division is useful for supporting new discovery on energy and mineral resources, environmental geology, and geologic hazard mitigation. Â